A Bibliographic Analysis of the Development of a Blended Learning Model Based on LMS to Improve Students’ Writing Skills - Dewi, Novi Triana; Bintoro, Totok; Rafli, Zainal (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Blended learning is an instructional model that combines face-to-face learning with e-learning through a Learning Management System (LMS). One of the subjects that can be taught using the blended learning model is writing skills. This study aims to analyze keywords, authors’ origins, and sources of references in research journal articles concerning the development of a blended learning model based on LMS to enhance students’ writing skills in Indonesia. The research method used is bibliometric analysis with the aid of the Publish or Perish software, focusing on research articles published and indexed by Scopus from 2015 to 2025. Data analysis was conducted using descriptive-analytic methods with the VOSviewer system and MS Excel. The results show that there are 150 research articles indicating that blended learning can improve students’ writing skills. Ten top journals were identified as major publishers of research on LMS-based blended learning, along with eight leading authors on the topic. The visualization of relationships revealed seven items with a total link strength of 30. The overlay visualization indicates relationships among authors in articles on instructional models. The conclusion of the study suggests that quantitatively, research on blended learning related to students’ writing skills is still limited. Further studies and in-depth analyses are needed to identify specific variables and provide more comprehensive discussions on how blended learning can improve students’ writing skills.